Genome-wide transcriptional response of microRNAs to the benzo(a)pyrene stress in amphioxus Branchiostoma belcheri. (March 2019) - Zhang, Qi-Lin; Dong, Zhi-Xiang; Xiong, Yan; Li, Hong-Wei; Guo, Jun; Wang, Feng; Deng, Xian-Yu; Chen, Jun-Yuan; Lin, Lian-Bing
Abstract: Amphioxus, a cephalochordate found in sand habitats in shallow in-shore seawaters, has been widely used as a model in comparative immunology of chordates. However, the role of microRNAs (miRNAs) in amphioxus under abiotic stress, particularly xenobiotics with strong toxicity, remains largely unknown. Here, a widespread marine contaminant, benzo(a)pyrene (BaP) is used to evaluate its toxic effects on miRNA expression of amphioxus. Six small RNA libraries were sequenced from Branchiostoma belcheri . A total of 144 known and 157 novel miRNAs were identified using deep sequencing and bioinformatics approaches. A total of 58 differentially expressed miRNAs (DEMs) were screened, including 25 up- and 33 down-regulated DEMs under BaP stress. Target genes possibly regulated by DEMs were predicted, and their functional enrichment analyses were performed. Targets of DEMs are primarily involved in xenobiotic and cellular homeostasis, catabolic and transport process. They could be largely linked to nine immune- and toxin detoxification-related pathways, including metabolism of xenobiotics by cytochrome P450, drug metabolism-other enzymes, and drug metabolism-cytochrome P450, etc. Furthermore, quantitative real-time PCR (qRT-PCR) analysis for 12 key BaP-responsive DEMs validates the accuracy of deep sequencing. Experiments were then conducted to investigate their expression responses to BaP stress at different time intervals in detail to further determine their expression dynamic in responses of B. belcheri towards BaP exposure. This study, to the best of our knowledge, investigates the regulatory roles of miRNAs in the toxicological response of amphioxus for the first time, providing valuable information for the protection of lone existing cephalochordate amphioxus. Highlights: We identified 58 differently expressed miRNAs in B. belcheri treated by BaP. BaP affected xenobiotic and cellular homeostasis, catabolic and transport process. Immune- and toxin detoxification-related pathways affected by BaP were identified. Expression response of amphioxus miRNAs to toxic stress was investigated firstly.